Variation of Tea Waste Addition on Bacterial Cellulose Production from Kombucha Fermented Sago Liquid Waste - Syarif, Fadla Binti; Permata, Deivy Andhika; Rahmi, Ira Desri (Journal of Fibers and Polymer Composites, 2025)
Sago liquid waste contains high levels of carbohydrates and has potential as a fermentation medium for bacterial cellulose production. However, its nutritional content requires enhancement by supplementing it with tea waste to achieve optimal yields. This study investigated the effect of varying tea waste additions on the characteristics of bacterial cellulose produced from kombucha fermentation based on sago liquid waste. The research method used a completely randomized design with five treatments (2, 4, 6, 8, and 10 g of tea dregs) and three replications. The observed parameters included yield, thickness, moisture content, cellulose content, and Fourier Transform Infrared (FTIR) spectroscopy. The results showed that increasing tea waste levels significantly affected all parameters (p < 0.05). The best treatment (10 g) resulted in a yield of 18.21%, a thickness of 13.47 mm, a moisture content of 47.57%, and a cellulose content of 52.43%. FTIR spectral analysis confirmed the characteristic peaks of bacterial cellulose, indicating the presence of crystalline β-1,4-glucan structures. The identification of cellulose type I is significant because it represents the native crystalline form of bacterial cellulose, which is associated with high mechanical stability, strong hydrogen bonding, and potential suitability for biopolymer applications. This study demonstrates that tea waste is an effective nutrient supplement that enhances the quality and quantity of bacterial cellulose derived from kombucha fermentation of sago liquid waste.